Association between BMI and plantar fasciitis among hospital staff in a selected hospital of Dhaka city - Al-Ansary, Mohammad Yaqub; Rahman, Mohammad Habibur; Kakuli, Samena Akter; Kabir, Mohammad Feroz; Ali, Mohammad Ershad (International Journal Of Community Medicine And Public Health, 2023)
Background: Plantar fasciitis described as the inflammation of planter fascia, particularly hampering an individual’s daily living activities related to ankle and foot that impact on quality of life. The study aimed to identify the association between BMI and planter fasciitis among hospital staff in a selected hospital in Dhaka city. Methods: A descriptive cross-sectional study. Results: Mean±SD age of the respondents were 29.03±6.56 years. Among the hospital staff, the majority of the respondents were nurses 31.25%, 13.02% respondents were physician and 2.07% of respondents were physiotherapists, others were pharmacist, lab technician, administration staff, cleaner, security, information technologists and officers from the maintenance department of selected hospital. According to BMI scale the 65% were normal weight, 23% were overweight and only 12% were obese. In this study respondents who have only two family members, have strong relationships with BMI (p<0.00). Besides, the duration of work has a slightly significant relation with BMI (p<0.03) and BMI has a strong impact on level of pain (p<0.01) among respondents. Conclusions: The recommendation for risk variables that have a strong correlation with plantar fasciitis is the working status, duration, and BMI.